Humans as biodiversity engineers: trait-based approaches to understand human impact on temporal changes in plant communities - Veeken, Annegreet (2023)
Although the current human impact on ecosystems is unprecedented, human activities have been altering ecosystems for millennia. The temporal domain in ecology is understudied but increasingly recognised for its relevance to comprehending natural dynamics and contextualising recent biodiversity change. Understanding how human activities shape plant communities, spatially and temporally, is crucial to anticipate possible undesirable consequences. Because plants are central to maintaining ecosystem functioning, changes in species composition might alter ecosystem functioning and affect human well-being. However, the links between human impact, species composition and ecosystem functioning are challenging to grasp when solely studying species composition. Trait-based approaches in ecology allow for a greater understanding of relationships between human impact, species composition and ecosystem functioning. In this thesis, trait-based approaches are applied in novel ways to understand how humans shape plant composition over long time scales. Pollen records are the main source of information on past plant composition. Using the trait-based approach to reconstruct plant functional composition from pollen records, might allow for the extension of the time scales of functional ecology. In Paper 1 I tested the reliability of using pollen records for reconstructing past plant trait composition. I compared plant trait composition reconstructions based on modern pollen samples with the trait composition of the surrounding vegetation. I found there was high uncertainty in the relationship between vegetation trait composition and pollen-based trait reconstructions. Because of the low sample size in this study, a possible positive relationship between pollen-based reconstructions and vegetation trait composition is not ruled out. However, these results advocate for carefully trait variation within pollen taxa and encourage further testing of the trait-based approach in palaeoecology. In Paper 2 I examined how the start of agriculture changed plant functional composition in Europe. To reconstruct plant functional composition from 78 pollen records, I used a novel Bayesian approach to include trait variation within pollen taxa. I demonstrated a four-fold decrease in whole plant size since the beginning of agriculture. Especially in the last 2000 years, a trend towards the acquisitive end of the leaf economic spectrum was shown. Both agriculture and climate may have played a role in this trend. These results indicate that by modifying plant functional composition, early agriculture might have significantly impacted biogeochemical cycles. In Paper 3 I tested if life-history traits can explain relatively recent population-level and community-level changes using the global biodiversity database BioTIME. I did not demonstrate a relationship between life-history, human impact and population change. To test how life-history influences community-level changes, I calculated species’ contribution to turnover. Life-history traits are important predictors of contribution to turnover, but these effects are conditional on the degree of human use and climate change intensity. Knowing the traits and population changes of species that are strong contributors to turnover, could lead to a better understanding of the processes that drive biodiversity change. Together, this thesis demonstrates novel ways to use traits for understanding human impacts on plant communities in the temporal domain. It shows that there are challenges in applying traits to understand temporal changes in plant communities, but also that there are new insights to be gained from it.